Peran Guru Pendidikan Agama Islam pada Program Sekolah Penggerak di SD Negeri 03 Kandis - Fikri Shobri; Alfurqan Alfurqan (Journal on Education, 2023)
This research focuses on the role of the Islamic Religious Education teacher in the driving school program whose aim is to find out the role of the Islamic Religious Education teacher in the driving school. This type of research is field research (field research) which is descriptive in nature with a qualitative approach, namely conducting research directly to the location to obtain and collect data. The research location is Kandis 03 Public Elementary School. The subject of this study involved all components in the driving school, especially Islamic Religious Education Teachers. The results of the study show that the driving school program at SDN 03 Kandis focuses on improving student learning outcomes through the implementation of project learning. This begins with building and developing the performance of the Principal and teachers. The role of the Islamic Religious Education Teacher in general is to support all matters relating to the driving school program. Islamic Religious Education teachers have a very important role in supporting the implementation of the driving school program at Kandis 03 Public Elementary School, including; becoming a school committee, carrying out religious activities and full self-development on Fridays and carrying out the 5P program (Project of Strengthening Pancasila Student Profiles) . The obstacles faced by Islamic Religious Education teachers at SDN 03 Kandis are related to administrative burdens that take up time, attention and energy. The solution is that Islamic Religious Education teachers must improve the six competencies of Islamic Religious Education teachers including (Pedagogical competencies, social competencies, personality competencies, professional competencies, leadership competencies and spiritual competencies) and work smart by utilizing digitalization as time efficiency in fulfilling several regulations from the government .